18F-FDG PET/CT for Molecular Imaging of Hepatoblastoma in Beckwith-Wiedemann Syndrome. (May 2018) - Derlin, Thorsten; Hartung, Dagmar; Hueper, Katja
Abstract : Abstract: Beckwith-Wiedemann syndrome (BWS) is a rare congenital overgrowth disorder variably characterized by macrosomia, macroglossia, congenital hypoglycemia, and hemihyperplasia. The BWS predisposes affected individuals to embryonal tumors during childhood. The BWS is caused by abnormal gene regulation in a particular region of chromosome 11. We present the case of a 1-year-old boy with BWS who underwent an 18 F-FDG PET/CT scan for restaging of hepatoblastoma. On the 18 F-FDG PET scan, increased tracer accumulation was observed in hepatoblastoma lesions. In addition, marked hemihyperplasia was noted. This case highlights the usefulness of 18 F-FDG PET/CT for restaging of hepatoblastoma in BWS.